2016
DOI: 10.20885/teknoin.vol22.iss2.art5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Dan Perencanaan Mitigasi Resiko Proyek Pembangunan Jalur Ganda Kereta Api Semarang - Bojonegoro

Abstract: Calista Perkasa Mulia ( CPM ) ltd is a contracting company of the railway construction. In the project construction of double track railway Semarang-Bojonegoro period April 2012 to December 2013 , scheduling and risk management has not been implemented properly. It could been seen from the works that was not completed on schedule. Therefore, the purpose of this study was to design a project scheduling with precedence diagram method (PDM) and risk management. The results showed that one of the strategies which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Most of the findings of the current study were also found in previous reports with regard to project's success factors. The emerged theme of risk management and its components were similar to those of reported by Hyvari (2006), and also Munang and Faisal (2016) that risk management was an extremely important aspect to be managed properly in each stages of the projects. Other finding similarities can also be observed on the project's success factor regarding resource controlling as reported by Isik et al (2010), and Plant and Willcocks (2007), which stated that the avalability of needed resources was vital for projects' success.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Most of the findings of the current study were also found in previous reports with regard to project's success factors. The emerged theme of risk management and its components were similar to those of reported by Hyvari (2006), and also Munang and Faisal (2016) that risk management was an extremely important aspect to be managed properly in each stages of the projects. Other finding similarities can also be observed on the project's success factor regarding resource controlling as reported by Isik et al (2010), and Plant and Willcocks (2007), which stated that the avalability of needed resources was vital for projects' success.…”
Section: Discussionsupporting
confidence: 71%
“…A detailed project planning, which encompassed by clear goals will result in clarity of project' scope, expected results, and activities in the endeavor to achieve project success (Buddas, 2014;Ika, Diallo & Thuillier, 2012). When the project's development would not progress according to the plan, then sufficient risks' identifications, mitigations, and contingency plans will serve their roles to secure the project success (Hyvari, 2006;Munang & Faisal, 2016). Management of project's time, quality, cost, resources, planning, and risks were the project's success factors reported in general scopes.…”
Section: Project's Success Factorsmentioning
confidence: 99%
“…Lampu LED memiliki usia pakai dan efisiensi listrik beberapa kali lipat lebih balik daripada lampu pijar dan tetap jauh lebih efisien daripada lampu neon, beberapa chip bahkan dapat menghasilkan lebih dari 300 lumen per watt. Lampu LED hanya butuh energi sebesar 10% dari energi yang dibutuhkan lampu pijar (Munang et al,2016). Tidak seperti lampu pijar dan lampu neon, lampu LED akan menghasilkan terang sepenuhnya tanpa perlu waktu pemanasan (warm-up) Lampu LED terbuat dari plastik dan diode semikonduktor yang dapat menyala apabila dialiri tegangan listrik rendah (sekitar 1,5 volt DC).…”
Section: Aspek Teoritisunclassified
“…An integrated approach of interpretive rating process (IRP) and dynamic system (SD) for modeling the main risk factors of construction projects can facilitate in designing risk mitigation strategies (Mhatre et al, 2017). The risk of the double-track railway project is quite high with 19 unexpected risks and 12 acceptable risks (Munang et al, 2016). The work with the highest accident risk value is monitored and repaired to reduce the accident rate.…”
Section: Introductionmentioning
confidence: 99%